2019
DOI: 10.3390/app9173544
|View full text |Cite
|
Sign up to set email alerts
|

Proposal of Laser-Induced Ultrasonic Guided Wave for Corrosion Detection of Reinforced Concrete Structures in Fukushima Daiichi Nuclear Power Plant Decommissioning Site

Abstract: Remote-controlled, non-destructive testing is necessary to detect corrosion of the reinforced concrete structures at the Fukushima Daiichi Nuclear Power Plant (NPP) de-commissioning site. This work aims to demonstrate that laser-induced ultrasonic guided wave technology can be applied to achieve this task. Hence, accelerated electrolytic corrosion is performed on a reinforced concrete specimen fabricated by embedding a steel rod into mortar. Waveforms of the laser-induced ultrasonic guided wave on the rod are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“…Nowadays, in addition to the development of efficient corrosion protection technologies, timely and effective corrosion monitoring and detection technologies are also particularly important. For example, resistance probe technology, , fluorescence probe technology, ultrasound monitoring technology, field fingerprint online wall thickness monitoring technology, , nondestructive diagnosis pulse eddy current technology, etc., provide an important basis for scientific management and decision-making. On the one hand, these technologies can be used to monitor the corrosion status of the medium, identify problems in a timely manner, and prevent the occurrence of major accidents.…”
Section: Other Carbon Materialsmentioning
confidence: 99%
“…Nowadays, in addition to the development of efficient corrosion protection technologies, timely and effective corrosion monitoring and detection technologies are also particularly important. For example, resistance probe technology, , fluorescence probe technology, ultrasound monitoring technology, field fingerprint online wall thickness monitoring technology, , nondestructive diagnosis pulse eddy current technology, etc., provide an important basis for scientific management and decision-making. On the one hand, these technologies can be used to monitor the corrosion status of the medium, identify problems in a timely manner, and prevent the occurrence of major accidents.…”
Section: Other Carbon Materialsmentioning
confidence: 99%
“…As for remotely detecting elastic waves propagated through concrete, non-contact acoustic systems with a laser doppler vibrometer (LDV) for detecting signals have been reported [13][14][15]. These research approaches provide remote and rapid operations for inspection works based on the elastic wave method.…”
Section: Remote Sensing For Elastic Wave Detection With Laser Dopplermentioning
confidence: 99%
“…Toyama et al demonstrated a rapid non-contact ultrasonic inspection technique by visualization of Lamb wave propagation for detecting barely visible impact damage (BVID) in carbon fiber reinforced polymer (CFRP) laminates [26]. Furusawa et al utilized laser-induced ultrasonic guided wave technology to detect corrosion of the reinforced concrete structures [27]. Liu et al presented a non-destructive damage detection, visualization, and quantification technique based on laser-generated ultrasonics and state-space predictive models [28].…”
Section: Introductionmentioning
confidence: 99%